2020
DOI: 10.1002/anie.202009776
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Oxidation State of Pt Single Atoms for Maximizing Catalytic Activity

Abstract: Single-atom catalysts (SACs) have emerged as promising materials in heterogeneous catalysis.P revious studies reported controversial results about the relative level in activity for SACs and nanoparticles (NPs). These works have focused on the effect of metal atom arrangement, without considering the oxidation state of the SACs.H ere,w e immobilized Pt single atoms on defective ceria and controlled the oxidation state of Pt SACs,f rom highly oxidized (Pt 0 : 16.6 at %) to highly metallic states (Pt 0 :8 3.8 at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
100
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(105 citation statements)
references
References 44 publications
5
100
0
Order By: Relevance
“…Combination with the catalytic performance in Fig. 3a and previous reported 31 , 39 , the lower oxidized state of Pt species is appropriate for lower temperature CO oxidation. XANES data in Fig.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Combination with the catalytic performance in Fig. 3a and previous reported 31 , 39 , the lower oxidized state of Pt species is appropriate for lower temperature CO oxidation. XANES data in Fig.…”
Section: Resultssupporting
confidence: 78%
“…When the catalysts were pretreated at 300 °C under air, Bi-free and Bi-promoted samples show almost same CO oxidation activity with complete CO conversion at ~220 °C (Supplementary Fig. 8 ), may due to poor ability to adsorb CO or overhigh valence of platinum species 31 . However, we found that hydrogen reduction significantly enhanced CO oxidation activity for Bi-promoted catalysts (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…When the catalysts were pretreated at 300 °C under air, Bi-free and Bi-promoted samples shows almost same CO oxidation activity with complete CO conversion at ~ 220 °C ( Supplementary Fig. 8), may due to poor ability to adsorb CO or overhigh valence of platinum species 24 . However, we found that hydrogen reduction signi cantly enhanced CO oxidation activity for Bipromoted catalysts (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…XANES data inFig. 4findicated platinum species are at low valence state after CO oxidation:Supplementary Table 2) due to hydrogen reduction, indicating lower oxidized state of Pt species are appropriate for lower temperature CO oxidation24,28 . In order to require more reliable local coordination structure for used Bi-promoted samples, we conducted the EXAFS tting process with or without Pt−O−Bi shell inSupplementary Fig.…”
mentioning
confidence: 99%
“…[99] Catalysts containing 1 wt% platinum were prepared on highly defective cerium oxide particles supported on alumina and shown by EXAFS spectra, IR spectra of adsorbed CO, and STEM images to incorporate atomically dispersed platinum. [26] The samples were reduced at various temperatures in 10% H 2 /N 2 , and XANES and XPS data showed that the platinum oxidation state decreased as the reduction temperature increased, with atomic dispersion being retained even at 300 °C for the entrapped platinum atoms-and the data suggested that the formal oxidation state was close to zero. The catalysts were tested for CO oxidation, methane combustion, and NO oxidation, with the sample reduced at 300 °C showing the highest degree of reduction of the platinum and the highest activity for each reaction.…”
Section: Catalysis By Atomically Dispersed Supported Platinummentioning
confidence: 96%